In vivo identification of mitral valve fibrosis and calcium by real-time quantitative ultrasonic analysis - Lattanzi, F; Picano, E; Landini, L; Mazzarisi, A; Pelosi, G; Benassi, A; Salvatore, L; Distante, A; L'Abbate, A (The American journal of cardiology, 1990)
Conventional echocardiography provides fundamental information about mitral valve morphology and function but has a relatively low specificity in evaluating valve calcific deposits, which is critical information for the preoperative decision to perform commisurotomy or replacement. In vitro radiofrequency ultrasonic quantitative analysis of the mitral valve has been demonstrated to be a reliable tool in identifying normal, fibrotic and calcific valves. This study evaluates quantitative ultrasound characterization of the mitral valve in vivo. Thirty-three patients, scheduled to undergo mitral valve replacement, and 20 normal subjects (10 young and 10 older control subjects) were studied with a 2.25-MHz transducer. Radiofrequency signal was analyzed by a microprocessor system (used with an M-mode commercially available echocardiograph) for on-line evaluation of ultrasonic backscatter with 8 bits of amplitude resolution, 40-MHz sampling rate and a 1-microsecond acquisition gate. The integrated value of the rectified radiofrequency signal amplitude was deemed the integrated backscatter index. The highest value recorded with the ultrasonic analysis from each valve was taken as representative and expressed as the percent value with respect to the pericardial integrated backscatter index value of that subject. The 33 excised mitral valves underwent histologic examination. Four groups were identified: young controls (group I, n = 10); older controls age-matched with patients (group II, n = 10); patients with fibrotic mitral valves (group III, n = 13); and patients with calcific mitral valves (group IV, n = 20).